Exploring public sector planning for transformational government. Issue 3 (2nd October 2017) - Mawela, Tendani; Twinomurinzi, Hossana; Ochara, Nixon Muganda
Abstract : Purpose: This paper aims to understand the conceptualisation of the notion of transformational government that is emerging within the electronic government domain. It reviewed how transformational government is manifest in the policy and strategic commitments of government departments in South Africa. The study focused on understanding the role of public sector planning towards the attainment of transformational government. Design/methodology/approach: The study is interpretive and qualitative in nature. It provides the outcomes of a deductive thematic analysis conducted on strategic documents of government departments to explore their alignment and support for transformational government. Findings: The paper argues for the need for public sector planning that is focused on citizen benefit realisation. The results highlight the significance of strategic plans for developmental transformation. However, the planning instruments were found to have an inconsistent orientation towards transformational government. Originality/value: The study is significant in light of the implications of public policy and the associated strategic plans for citizens. This paper also contributes to research on the nascent area of transformational government.